Management Of Polycystic Ovarian Syndrome Through Ayurveda : A Case Study - Banappanavar, Malagouda K; Mathapati, Shweta; Rawal, P K; Shiraguppi, Sunita (International Research Journal of Ayurveda & Yoga, 2021)
Polycystic ovarian syndrome is the most common endocrine disorder in a woman of Reproductive age. It is manifested by amenorrhoea, hirsutism, obesity, enlarged polycystic ovaries, acne, elevated testosterone and androstenedione. It can be described as a state of hyper androgenise and chronic anovulation. The patient complains of increasing obesity (abdominal 50%), menstrual abnormalities (70% ) in the form of oligomenorrhoea , amenorrhea or dysfunctional uterine bleeding and infertility presence of hirsutism and acne are the important features, in classics PCOS can be correlated with Anartava ( Amenorrhea), Nastartava, Artava kshay ( Oligomenorrhea ), Vandya yonivyapat ( Infertility ), Pushpaghni, Jataharini ( Repeated abortion ) Granthibhuta artava dusti. A 20-year-old unmarried woman visited the OPD of department of PTSR of SDMT’s AMC Terdal on 19-09-2020. she had complained of Irregular menses, weight gain (79 kg) for two years, increased hair growth on the neck and face, and acne over the face.